Organofluorine compounds in biology and medicine - Reddy, V. Prakash (Amsterdam, Netherlands : Elsevier, 2015)
This book covers topics on biochemically relevant organofluorine compounds and their synthesis and biochemical pathways. Organofluorine compounds have renewed interest in pharmaceutical industry, and therefore a concise book on this topic is highly relevant to the scientific community involved in this area.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Organofluorine compounds; SCIENCE / Chemistry / Organic; Organofluorine compounds; Electronic books; Electronic books